Glycemic effects of simvastatin: Where do we stand? - Nor Razida Razali; Hasniza Zaman Huri; Luqman Ibrahim; Shireene Ratna Vethakkan; Bashar Mudhaffar Abdullah (Universidade de São Paulo, 2018)
ABSTRACT In clinical practice, simvastatin is usually used in the treatment of dyslipidemia patients and those at risk of or with established cardiovascular disease. However, previous studies have shown that simvastatin has the potential to affect glycemic parameters as it reportedly reduced insulin secretion and sensitivity. The exact mechanism by which simvastatin affects glycemia is still unknown, but previous studies have postulated the involvement of the glucose-insulin secretion mechanism. This review focuses on the effects of simvastatin, either alone or in combination with other lipid lowering agents, antidiabetics and antihypertensives, on glucose homeostasis. Some studies have reported that simvastatin might impair the levels of glucose metabolism markers in the blood while others have reported no effect or improvement in glycemia.